Pengaruh Konseling Dengan Leaflet Terhadap Pemilihan Metode KB Pada PUS Di Puskesmas Kebakkramat II - Widodo, Joey Anung Anindtya; Puspitasari, Novita (STIKES Karya Husada Kediri, 2025)
Family Planning (KB) is a program of the Indonesian government since 1970. This program aims to control population growth, limit birth rates, and regulate birth spacing so as to create a healthy and prosperous family. The purpose of this study was to determine the effect of family planning counseling can influence the selection of contraceptive installation methods in couples of childbearing age. Quantitative research method with quasi experiment. The population in this study were couples of childbearing age in the Working Area of Puskesmas Kebakkramat 2 which amounted to 4,085 people. The sample in this study were 98 samples. The sampling technique used was probability sampling type purposive sampling. The variables studied were independent variables, namely counseling and dependent contraceptives. The measuring instrument used was a knowledge questionnaire about contraception as many as 11 questions, the decision to choose contraception as many as 16 questions and 12 questions about attitudes about contraception. The analysis used, namely the paired t test statistical test, showed a p value in the intervention group of 0.000 (p value ≤ α 0.05), which means that there is a difference in the average knowledge before and after the intervention. In the control group, the results of the paired t test statistical test showed a p value of 0.000 (p value ≤ α 0.05), which means there is a difference in average knowledge before and after the intervention.